Psychological Interventions for Better Physical and Mental Health of School Children - Roy, Puja (JOURNAL OF INDIAN EDUCATION, 2019)
Urbanisation and advancement in technology has put new demands on the education system. Personal and social development are vital for children to grow into well-adjusted adults, apart from academic success. This research view focuses on the psychological interventions for shaping physical and mental health of school children. The idea of the school is seen as a learning community, where learning is constructed as a fundamentally social process. Relationships between teachers and students are associated with positive outcomes like increased motivation, achievement, feelings of belonging and affects in school. Family influences including parent-child relationships have been vastly investigated to assess their association with social, emotional and learning outcomes. The joint efforts of educational personnel, healthcare practitioners and mental health providers to successfully tackle the physical and mental health needs of children and even their families is felt strongly.